Rules and Regulations Governing the Public Parks within the City of Lowell 58 (1903) - (:unkn) unknown (My University, 1903)
It is forbidden to throw stones, balls or other missiles; to discharge or carry firearms, fire crackers, torpedoes or fire-works
Keywords: CARRY; DISCHARGE